Atypical Presentation of Rheumatic Fever: Isolated Hemichorea with Subclinical Carditis and No Joint Involvement - Orlando Pikatan; Dian Kusumastuti Anggraeni Putri; Sri Yenni Trisnawati; I Wayan Widyantara; I Gusti Agung Ayu Gita Lavenia (Universitas Airlangga, 2026)
Highlight: The clinical manifestation of the Sydenham chorea The mechanism of hemichorea in Sydenham chorea involves the antigen found throughout the body. ABSTRACT Introduction: Rheumatic fever (RF) is an autoimmune inflammatory disease that develops as a complication of a previous infection with group A beta-hemolytic Streptococcus (GABHS), typically following episodes of tonsillopharyngitis. Although its prevalence has decreased due to advances in medical treatment and improved living conditions, RF remains a major health issue in developing countries. Sydenham chorea (SC) is a well-known neurological complication of RF, which occasionally presents as hemichorea, a rare condition affecting only one side of the body. Therefore, early identification is important for initiating treatment promptly and preventing further complications. Case: A 12-year-old boy presented with involuntary, dance-like movements on the left side, following a fever. Laboratory tests showed elevated inflammatory markers and ASTO titers, suggesting a prior streptococcal infection. Imaging revealed left-sided pneumonia. Brain scans were normal, but echocardiography revealed mild mitral regurgitation, indicating subclinical carditis. The patient was diagnosed with RF complicated by hemichorea and was subsequently treated with benzathine penicillin, ceftriaxone, haloperidol, and valproic acid. Increasing the valproic acid dosage effectively resolved the symptoms. Conclusion: Rheumatic fever should be considered in children presenting with hemichorea, even in the absence of joint involvement or overt cardiac symptoms. Early diagnosis, adherence to the 2015 revised Jones criteria, and long-term antibiotic prophylaxis are crucial to prevent disease recurrence and complications.